2015
DOI: 10.1016/j.bbamcr.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Shared-intermediates in the biosynthesis of thio-cofactors: Mechanism and functions of cysteine desulfurases and sulfur acceptors

Abstract: Cysteine desulfurases utilize a PLP-dependent mechanism to catalyze the first step of sulfur mobilization in the biosynthesis of sulfur-containing cofactors. Sulfur activation and integration into thiocofactors involve complex mechanisms and intricate biosynthetic schemes. Cysteine desulfurases catalyze sulfur-transfer reactions from l-cysteine to sulfur acceptor molecules participating in the biosynthesis of thio-cofactors, including Fe-S clusters, thionucleosides, thiamin, biotin, and molybdenum cofactor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 119 publications
0
106
0
Order By: Relevance
“…In Gram-negative E. coli , which uses the housekeeping IscS for sulfur mobilization to all thiocofactors [11,53,54], the Tus proteins also participate in additional metabolic pathways [71,175,176,177]. The multi-functionality of these and other enzymes in thiocofactor pathways has been attributed to the utilization of one major cysteine desulfurase (i.e., IscS) for all thiocofactors in Gram-negative bacteria and simultaneously demonstrates the resulting complexity of sulfur trafficking in these organisms [178,179]. The recruitment of small sulfur acceptor proteins or sulfurtransferase domains within individual pathways can be seen as a mechanistic strategy for controlling sulfur flux in organisms such as E. coli that utilize a master sulfur donor.…”
Section: Biosynthesis Of Thionucleosides In Bacterial Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…In Gram-negative E. coli , which uses the housekeeping IscS for sulfur mobilization to all thiocofactors [11,53,54], the Tus proteins also participate in additional metabolic pathways [71,175,176,177]. The multi-functionality of these and other enzymes in thiocofactor pathways has been attributed to the utilization of one major cysteine desulfurase (i.e., IscS) for all thiocofactors in Gram-negative bacteria and simultaneously demonstrates the resulting complexity of sulfur trafficking in these organisms [178,179]. The recruitment of small sulfur acceptor proteins or sulfurtransferase domains within individual pathways can be seen as a mechanistic strategy for controlling sulfur flux in organisms such as E. coli that utilize a master sulfur donor.…”
Section: Biosynthesis Of Thionucleosides In Bacterial Trnamentioning
confidence: 99%
“…Recent studies have revealed that thio-modifications participate in other cellular processes, including metabolism, stress response, and regulatory functions [24]. Several recent models have proposed interconnectivity between biosynthesis of thionucleosides and other thiocofactors in bacteria, providing another potential regulatory mechanism for thiocofactor biosynthesis [178,179]. In E. coli , s 2 C and ms 2 i 6 A biosynthetic pathways utilize [Fe-S] cluster dependent proteins, as do the pathways for ms 2 i 6 A and ms 2 t 6 A biosyntheses in B. subtilis .…”
Section: Interconnectivity Between Trna Modification and Biosynthementioning
confidence: 99%
“…During catalysis, the enzyme forms a covalent-persulfide intermediate, which serves as a hub for sulfur delivery in the biosynthesis of several thio-cofactors not limited to s 2 U formation (12). The versatility of IscS, which participates in multiple pathways, has been associated with its ability to interact with and transfer sulfur to a variety of sulfur acceptor molecules.…”
mentioning
confidence: 99%
“…However, local structural differences with characteristic reactivities have been used to assign CDSs into two classes [3, 30]: class I includes IscS-like sequences and class II includes SufS- and CsdA-like sequences (Figure 1). Class I CDSs contain a sequence insertion of more than 10 residues just after the conserved catalytic Cys, and class II CDSs contain a shorter insertion after the conserved catalytic Lys.…”
Section: Resultsmentioning
confidence: 99%